Current and emerging treatment options for pediatric eosinophilic esophagitis - Elitsur Y (Dove Medical Press, 2013)
Yoram ElitsurDepartment of Pediatrics, Gastroenterology Division, Marshall University, John C Edwards School of Medicine, Huntington, WV, USAAbstract: Eosinophilic esophagitis is a new clinicopathologic disorder and has been recognized as a chronic disease in children and adults. The disease is associated with environmental and food allergies, but the exact pathophysiology has not yet been discovered. Epidemiological studies showed a global distribution of the disease and an uneven geographic distribution within the United States where the northeastern states had a higher rate of prevalence compared to the western states. Studies have shown that there are multiple confounding factors that affect the phenotypic characteristics of the disease which may include place of residence (rural versus urban), ethnicity, race, and genetics, among others. Clinical presentation may be different between adult and pediatric patients, but the endoscopic and histological characteristics of the disease are very similar between those groups. The pathophysiology of the disease has not yet been established, but the mucosal immune system, especially the pathway involving the eosinophil lineage, has been suggested as taking a major role in the pathophysiology. Accordingly, the suggested therapeutic options for this disease include elimination diets, steroids, and anti-eosinophil medications. Unfortunately, those treatment options are limited by their efficacy and the side effects associated with their chronic use. In the current review, we describe the characteristics of eosinophilic esophagitis and present the available treatments and their pitfalls. We also speculate on the future development of new treatment for this chronic disease.Keywords: eosinophilic esophagitis, treatment, children, review